Modern spatiotemporal geostatistics - Christakos, George (Dover Publications, 2012)
" This introductory scholarly treatment explores the fundamentals of modern geostatistics, a group of spatiotemporal concepts and methods related to the advancement of the epistemic status of stochastic data analysis. Christakos considers the role of geostatistics in improved mathematical models of scientific mapping, and focuses on the Bayesian maximum entropy approach for studying spatiotemporal distributions of natural variables. 2000 edition"-- Provided by publisher.
Originally published: Oxford ; New York : Oxford University Press, 2000.
Keywords: Earth sciences -- Statistical methods.; Maximum entropy method.; Bayesian statistical decision theory.; elektronické knihy; electronic books